2015
DOI: 10.1016/j.neuroimage.2014.10.043
|View full text |Cite
|
Sign up to set email alerts
|

Empathic concern drives costly altruism

Abstract: Why do we self-sacrifice to help others in distress? Two competing theories have emerged, one suggesting that prosocial behavior is primarily motivated by feelings of empathic other-oriented concern, the other that we help mainly because we are egoistically focused on reducing our own discomfort. Here we explore the relationship between costly altruism and these two sub-processes of empathy, specifically drawing on the caregiving model to test the theory that trait empathic concern (e.g. general tendency to ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
212
4
11

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 274 publications
(240 citation statements)
references
References 70 publications
(121 reference statements)
13
212
4
11
Order By: Relevance
“…Ambiguity resolution is a process associated with the caudate as evidenced by fMRI paradigms with healthy individuals (O’Doherty, 2011; Ketteler et al, 2008). fMRI studies demonstrate that the caudate is recruited when an individual is deciding whether to perform an altruistic helping behavior or a non-helping behavior (FeldmanHall et al, 2015). Also, resolving ambiguity and making a decision to act or refuse to act may in itself be rewarding (Aupperle et al, 2015; Soares et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Ambiguity resolution is a process associated with the caudate as evidenced by fMRI paradigms with healthy individuals (O’Doherty, 2011; Ketteler et al, 2008). fMRI studies demonstrate that the caudate is recruited when an individual is deciding whether to perform an altruistic helping behavior or a non-helping behavior (FeldmanHall et al, 2015). Also, resolving ambiguity and making a decision to act or refuse to act may in itself be rewarding (Aupperle et al, 2015; Soares et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Altruism is a prosocial behavior that is driven by concern for others rather than concern for oneself and is accompanied with inherent personal costs (e.g., personal risk during the action or as an outcome, opportunity cost) (Eisenberg, 2014). Empathy and perspective-taking are socio-cognitive processes that are central to evoking altruistic behaviors (Eisenberg, Eggum, & Di Giunta, 2010), and rely on common neural circuitry (FeldmanHall, Dalgleish, Evans, & Mobbs, 2015). Interestingly, individuals high in altruism engage in neural networks related to empathy and theory of mind more so than individuals who are less altruistic (Haas et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, individuals high in altruism engage in neural networks related to empathy and theory of mind more so than individuals who are less altruistic (Haas et al, 2015). FeldmanHall et al (2015) reported that altruistic behavior is predicted by increased empathic concern for others but not by levels of personal distress. Previous research examining the relation between early childhood trauma and empathic abilities support our observation of reduced altruistic behaviors in patients with PTSD.…”
Section: Discussionmentioning
confidence: 99%
“…The vmPFC, together with the ventral striatum, amygdala and insula, is a part of a domain-general valuation system that processes significant and motivating information, and guides (both social and non-social) decision-making [57]. A recent neuroimaging study found that individuals high in dispositional empathic concern engaged in costly altruism, and this relationship was supported by neural activity in the ventral tegmental area, caudate and vmPFC [58]. Thus, caring for others piggybacks on older evolutionary motivational mechanisms associated with parental care.…”
Section: (B) Why Empathy Has Evolvedmentioning
confidence: 99%